THE IMPLEMENTATION OF TEAM TEACHING LEARNING METHOD ON ISLAMIC EDUCATION SUBJECT IN KUPANG ELEMENTARY SCHOOL - Fajeri Arkiang; Rabiatun Adwiah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aimed to determine the implementation of team teaching-learning method on Islamic education subject in Kupang elementary school. This type of research was field research with a qualitative research method. The research took place at SDN 1 Bonipoi Kupang with the subjects of the study were the principal, 2 PAI teachers, and 49 fifth grade students. The data collection techniques used were interviews, observation, and documentation. The result showed that the team teaching method applied at SDN 1 Bonipoi Kupang was a full team teaching, where all learning activities were carried out jointly by the team teaching teacher, starting from the planning, implementation, and evaluation stages as well as the division of roles, tasks, and teach responsibility. This team teaching method was very helpful for teachers and students in learning because 2 teachers collaborated with each other and worked together in the learning process in class in such a way that led to the creation of effective and efficient learning.